Identification of Mineral Potential in Galang District Tolitoli Regency Using the Method of Resistance and Induced Polarization - Adya Nur Syafitri Wijaya; Tati Zera; Nur Hidayat (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
Geologically, the province of Central Sulawesi is composed of various types of rocks, both in the form of igneous, sedimentary and metamorphic rocks. Regarding Central Sulawesi Province, mineral resources both metal and non-metal are quite varied. Increasing demand and demand for minerals, both metals, and non-metals. Research conducted to study the mineral potential in one of the regencies in Central Sulawesi Province. This research was conducted in Galang Sub-district, Tolitoli Regency, and Central Sulawesi Province by using the resistivity method and the Induced Polarization (IP) method with the Wenner-Schlumberger arrangement consisting of eight lines. The IP method is very accurate to discuss the potential of minerals that are below the surface. The inversion process does data processing in order to obtain the actual form of resistivity and chargeability modeling. Based on the modeling, the mineral potential in Galang Sub-district, Tolitoli Regency, Central Sulawesi Province is mostly found in all trajectories namely lane 01; 02; 04; 05; 05; 06; 07. Which is marked by a very high chargeability value between 300 msec - 500 msec. The research area also discusses granite and andesite, which have high resistivity values, between 2000 Ωm – 400000 Ωm.